A soft-packaged lithium carbon fluoride primary battery
Through the parallel connection of cylindrical pole group and multi-pole ear current-collection design, combined with the soft shell, the polarization problems caused by volume changes and high temperature during the discharge process of lithium fluoride carbon batteries are solved, and lithium with high specific energy and safety performance is achieved Fluorinated carbon battery, supports high power discharge and reduces assembly complexity.
Patent Information
- Application Number
- CN202010736445.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2040-07-28
Smart Images

Figure CN112038650B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium carbon fluoride primary batteries, in particular to a power-type square structure soft-package lithium carbon fluoride primary battery. Background Art
[0002] Lithium / carbon fluoride (Li / CF x ) battery is the first solid positive electrode lithium primary battery as a commodity. Because its theoretical mass specific energy is 2180Wh / kg, the highest in the positive electrode series, it has good high temperature performance and safety performance, a high and stable discharge platform, and a low self-discharge rate, it has always received great attention. The soft-package lithium carbon fluoride battery has a significant advantage in specific energy compared to metal shell batteries due to its lightweight shell, and its flexible size and excellent safety performance are the most promising and currently the most researched battery.
[0003] During the discharge process of lithium carbon fluoride primary batteries, the positive electrode active material carbon fluoride reacts with lithium ions to generate lithium fluoride and carbon, resulting in a significant increase in the thickness of the positive electrode. Conventional square soft-package structure lithium carbon fluoride primary batteries cannot effectively restrain the expansion of the pole piece due to the low shell strength. As the reaction proceeds, the distance between the electrode and the diaphragm gradually increases, resulting in an increase in polarization in the later stage of discharge, and the battery capacity cannot be effectively exerted. On the other hand, lithium carbon fluoride batteries generate a lot of heat when discharging at a high rate, which increases the internal temperature of the battery (up to about 100°C). At higher temperatures and without external forces, the contact between the pole piece and the diaphragm is worse, and the polarization phenomenon is further aggravated, resulting in a lower discharge platform. This is one of the bottlenecks that currently prevent lithium carbon fluoride primary batteries from discharging at high power. Summary of the invention
[0004] In view of this, the purpose of the present invention is to solve the deficiencies in the prior art and provide a soft-packaged lithium carbon fluoride primary battery.
[0005] The soft-packaged lithium carbon fluoride primary battery provided by the present invention is composed of a plurality of cylindrical electrode groups, a non-aqueous electrolyte, a glue-containing electrode ear and a shell. The plurality of cylindrical electrode groups are in parallel with each other, and the cylindrical electrode group is composed of a positive electrode sheet, a negative electrode sheet and a separator; the outer circle of the cylindrical electrode group is wrapped with 2-5 turns of termination tape, preferably 2-3 turns.
[0006] The base material of the termination tape includes common materials for film tapes such as polyimide (PI), polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), and polyvinyl chloride (PVC).
[0007] The current collecting method of the positive electrode sheet and the negative electrode sheet is to set up multiple pole tabs for current collection or reserve continuous foil as pole tabs for current collection; the pole tabs for current collection of the positive and negative electrode sheets are respectively located on both sides of the cylindrical electrode group along the axial direction.
[0008] The multiple pole ears in the positive electrode sheet are evenly arranged in the positive electrode sheet, and are connected to the positive electrode sheet current collector by ultrasonic welding process. The material of the pole ears is aluminum, and the positive electrode sheet current collector is aluminum foil or carbon-coated aluminum foil; the connection between the multiple pole ears is carried out by converging with aluminum strips, and the connection method between the multiple pole ears or the converging aluminum strips and the glue-containing pole ears is ultrasonic welding or laser welding.
[0009] The multiple pole tabs in the negative electrode sheet are evenly arranged in the negative electrode sheet, and are bonded to the negative electrode metal lithium by a pressing process, or are connected to the negative electrode current collector by an ultrasonic welding process; the negative electrode current collector is copper foil or perforated copper foil; the material of the pole tabs includes nickel, copper, and copper-plated nickel; the connection between the multiple pole tabs is carried out by converging nickel strips, copper strips, and copper-plated nickel strips, and the connection method between the pole tabs or converging strips and the glue-containing pole tabs is ultrasonic welding or laser welding.
[0010] The active material of the positive electrode sheet is mainly composed of carbon fluoride, which may include a mixture of carbon fluoride and an oxide with electrochemical activity; the mass proportion of carbon fluoride in the mixture is 20%-100%.
[0011] The fluorinated carbon includes fluorinated hard carbon, fluorinated soft carbon, fluorinated amorphous carbon, fluorinated artificial graphite, fluorinated natural graphite, fluorinated graphene, fluorinated carbon fiber, fluorinated carbon nanotubes, fluorinated carbon microspheres, fluorinated activated carbon or fluorinated carbon black, among which fluorinated hard carbon and fluorinated soft carbon are preferred; the F / C atomic ratio in the fluorinated carbon is 0.4-1.0, and the preferred F / C atomic ratio is 0.75-0.95; the F / C atomic ratio is distributed in a gradient in the material particles, and the F / C atomic ratio of the outermost layer of the particles is close to 0, that is, the outermost layer of the material particles is carbon with good conductivity, and the carbon layer thickness is 1-20nm; the fluorinated carbon has undergone surface modification treatment, and the surface modification treatment method is an in-situ surface fluorine removal method including a hydrothermal method and a plasma method.
[0012] The electrochemically active oxides include manganese dioxide MnO2, nickel oxide NiO, copper oxide CuO, vanadium pentoxide V2O5, silicon oxide SiO2, Ag2V4O 11 One or more substances that can react with lithium.
[0013] The active material of the negative electrode sheet is metallic lithium, including lithium alloys and pure metallic lithium, and the alloy elements include one or more of nickel Ni, cobalt Co, manganese Mn, aluminum Al, magnesium Mg, and zirconium Zr;
[0014] The shell is a soft shell, including an aluminum-plastic film or a steel-plastic film.
[0015] Compared with the prior art, the square structure soft-package lithium carbon fluoride primary battery provided by the present invention adopts cylindrical pole groups in parallel to achieve the predetermined square external dimensions and capacity requirements. The cylindrical pole group has inherent structural advantages such as the tight winding of the pole piece and the diaphragm due to the internal stress, and the termination tape wrapped around the outer ring can effectively restrain the volume change. During the process of the expansion of the positive pole piece and the reduction of the thickness of the negative pole piece during discharge, the good effect of the positive and negative pole pieces and the diaphragm are always in close contact, ensuring the full utilization of the battery capacity. At the same time, the drainage structure design of multiple pole ears and foil pole ears is adopted, which not only realizes the effect of uniform distribution of current density and reduced polarization inside the battery, but also can quickly and effectively guide the heat inside the battery, overcoming the problem that lithium carbon fluoride batteries cannot discharge at high power. In addition, the hot-melt sealing edge of the soft-package battery has a certain packaging strength. When the battery is overheated and produces gas, the hot-melt edge will be released, achieving the beneficial effect of rapidly reducing the internal pressure and temperature of the battery. Its safety performance is significantly better than that of conventional cylindrical batteries and steel-shell square batteries.
[0016] The battery of the present invention adopts a soft-packaged lightweight shell to give full play to the high specific energy and high safety characteristics of the lithium carbon fluoride battery. The battery does not deform or expand significantly during the entire discharge process. During use, there is no need to use a high-strength shell and clamps for restriction, which greatly reduces the difficulty of combined application and broadens the application market and application field of lithium carbon fluoride batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a schematic diagram of the appearance structure of the square soft-package lithium carbon fluoride primary battery described in Example 1;
[0018] Figure 2 This is a schematic diagram of the internal structure of the square soft-package lithium carbon fluoride primary battery described in Example 1;
[0019] Figure 2a yes Figure 2 Schematic diagram of the decomposition of the middle cylindrical pole group;
[0020] Figure 3 This is a schematic diagram of the appearance structure of the square soft-package lithium carbon fluoride primary battery described in Example 2;
[0021] Figure 4 This is a schematic diagram of the internal structure of the square soft-package lithium carbon fluoride primary battery described in Example 2;
[0022] Figure 5 This is a schematic diagram of the internal structure of the square soft-package lithium carbon fluoride primary battery described in Comparative Example 1;
[0023] Figure 60.5C discharge curves of the batteries prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2.
[0024] In the figure, 1 is a shell, 2 is a hot-melt packaging edge of the shell, 3 is a positive electrode ear of the battery containing glue, 4 is a thermal capacity glue of the positive electrode ear containing glue, 5 is a negative electrode ear of the battery containing glue, and 6 is a thermal capacity glue of the negative electrode ear containing glue;
[0025] 1-1 is the positive ear of the electrode group, 1-2 is the positive ear welding spot, 1-3 is the negative ear of the electrode group, 1-4 is the negative ear welding spot, 1-5 is the positive electrode sheet, 1-6 is the separator, 1-7 is the negative electrode sheet, 2-2 is the positive ear bus of the electrode group, and 2-4 is the negative ear bus of the electrode group. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the advantages of the technical solution of the present invention are illustrated below through specific embodiments and comparative examples.
[0027] Embodiment 1:
[0028] A wing-shaped soft-packaged square lithium carbon fluoride primary battery with tabs at both ends of the battery, which is composed of three cylindrical pole groups with a diameter of 18 mm connected in parallel internally, with a designed capacity of 7.8Ah. The schematic diagram of its appearance structure is shown in the figure Figure 1 The internal structure diagram is shown in Figure 2 shown. Figure 1 In the figure, the shell 1 is an aluminum-plastic film with a thickness of 110 μm; the width of the shell sealing hot-melt sealing edge 2 is about 4 mm; the specifications of the positive electrode glue-containing pole ear 3 and the negative electrode glue-containing pole ear 5 are 0.2 mm thick × 40 mm wide; the specifications of the thermal capacitance glue 4 of the positive electrode glue-containing pole ear and the thermal capacitance glue 6 of the negative electrode glue-containing pole ear are 0.2 mm thick × 46 mm wide × 8 mm high.
[0029] Figure 2 The specifications of the cylindrical electrode group are: diameter 18mm×height 60mm. The cylindrical electrode group consists of a positive electrode ear 1-1, a negative electrode ear 1-3, a positive electrode sheet 1-5, a separator 1-6, and a negative electrode sheet 1-7. The schematic diagram of the cylindrical electrode group is shown in Figure 2a .
[0030] Among them, the positive electrode sheet 1-5 is composed of a current collector and positive electrode powder, with a size of 107μm thick × 58mm wide * 610mm total length. Two 15mm wide blank aluminum foils are reserved near the 1 / 4 and 3 / 4 positions in the length direction for welding the positive electrode ear 1-1. The total length of the coated positive electrode powder is 580mm. The current collector is a 15μm thick carbon-coated aluminum foil; the positive electrode powder is composed of carbon fluoride, conductive agent and binder (the weight ratio of the three is 92:3:5), and the total double-sided loading of the positive electrode powder is 12mg / cm 2The fluorinated carbon is a fluorinated biomass hard carbon with an average particle size of about 6 μm, a rich multi-level pore structure, and a total specific surface area of about 600 m 2 / g, the F / C atomic ratio in the particles is about 0.8. After hydrothermal surface modification, the outermost layer of fluorinated carbon is reduced to carbon with good conductivity, the carbon layer thickness is about 3-5nm, and the gram capacity of fluorinated carbon material is about 700mAh / g (at 10 hour rate discharge). The positive electrode tab 1-1 is made of aluminum, with a size of 0.1mm thick × 4mm wide × 50mm long. There are two tabs in total, which are located near the 1 / 4 and 3 / 4 positions of the positive electrode sheet 1-5, respectively. The length of the exposed electrode sheet is about 8mm, and it is connected to the positive electrode sheet 1-5 using an ultrasonic welding process.
[0031] The negative electrode sheet 1-7 is continuous metal lithium, with dimensions of 0.05mm thick × 56mm wide * 630mm long. The negative electrode tab 1-3 is made of nickel, with dimensions of 0.07mm thick × 4mm wide × 50mm long. Two are also provided, located near the 1 / 4 and 3 / 4 positions of the negative electrode sheet 1-7, respectively. The length of the exposed tab is about 10mm, and it is bonded to the negative electrode lithium sheet by a pressing process.
[0032] The material of the diaphragm 1-6 is polyethylene (PE), and the dimensions are 16 μm thick × 60 mm wide × 1500 mm long.
[0033] The positive electrode sheet 1-5, separator 1-6, and negative electrode sheet 1-7 are wound around a cylindrical winding needle with a diameter of 3 mm, and the positive electrode ear 1-1 and the negative electrode ear 1-3 are respectively located at the two ends of the electrode group, and the separator is used to end; finally, three turns of the termination tape are wound around the outermost circle to fix the electrode group to form a cylindrical electrode group 1. The termination tape is made of polyimide (PI) and has a size of 50 μm thick × 56 mm wide.
[0034] The three cylindrical electrode groups 1 are arranged side by side, with the same polarity tabs on the same side, and the 0.2mm thick * 40mm wide aluminum tab 3 containing glue is connected to all the positive tabs 1-1 of the electrode group, and the 0.2mm thick * 40mm wide nickel tab 5 containing glue is connected to all the negative tabs 1-3 of the electrode group by ultrasonic welding. Finally, the connected battery is placed in the pit of the stamped aluminum-plastic film shell, and three sides are heat-sealed by a heat sealer, leaving the end for injection unsealed.
[0035] An electrolyte containing 1M LiBF4 lithium salt and PC and DME solvents was injected into the battery, and the injection amount was about 12g. After vacuum standing, the injection side of the battery was vacuum-sealed. Then it was placed in a 45°C high temperature box and vacuum-sealed after the electrolyte was fully infiltrated to obtain the battery of Example 1.
[0036] Embodiment 2:
[0037] A soft-packaged square lithium carbon fluoride primary battery with a tab at the same end of the battery, which is composed of three cylindrical pole groups with a diameter of 18 mm connected in parallel internally, with a designed capacity of 7.8Ah. The schematic diagram of its appearance structure is shown in the figure Figure 3 The internal structure diagram is shown in Figure 4 shown. Figure 3 In the figure, the shell 1 is an aluminum-plastic film with a thickness of 110 μm; the width of the shell sealing hot-melt sealing edge 2 is about 4 mm; the dimensions of the positive electrode glue-containing ear 3 and the negative electrode glue-containing ear 5 are 0.2 mm thick × 20 mm wide; the specifications of the thermal capacitance glue 4 of the positive electrode glue-containing ear and the thermal capacitance glue 6 of the negative electrode glue-containing ear are 0.2 mm thick × 26 mm wide × 8 mm high.
[0038] Figure 4 In the embodiment, the cylindrical electrode group has the specifications of: diameter 18 mm×height 60 mm, and the cylindrical electrode group is composed of a positive electrode tab 1-1, a negative electrode tab 1-3, a positive electrode sheet 1-5, a separator 1-6, and a negative electrode sheet 1-7. The manufacturing method of the cylindrical electrode group is exactly the same as that of Example 1.
[0039] The three cylindrical electrode groups 1 are arranged side by side, with the same polarity tabs on the same side, and the 0.2mm thick * 8mm wide L-shaped aluminum busbar (positive electrode) 2-2 is connected to all the positive tabs 1-1 of the electrode groups by ultrasonic welding, and the 0.2mm thick * 8mm wide L-shaped nickel busbar 2-4 is connected to all the negative tabs 1-3 of the electrode groups; then the positive electrode busbar 2-2 and the negative electrode busbar 2-4 are ultrasonically welded to the positive electrode tab 3 and the negative electrode tab 5 of the battery, respectively, and the tab substrates are aluminum and copper plated with nickel, respectively, and the substrate size is 0.2mm thick * 20mm wide, and the size of the thermal capacity glue 4 of the positive electrode tab and the thermal capacity glue 6 of the negative electrode tab is 0.2mm thick × 26mm wide × 8mm high. The connected battery is placed in the pit of the stamped aluminum-plastic film shell, and a heat sealer is used to heat seal the three sides, and the end reserved for injection is not sealed.
[0040] An electrolyte containing 1M LiBF4 lithium salt and PC and DME solvents was injected into the battery, and the injection amount was about 12g. After vacuum standing, the injection side of the battery was vacuum-sealed. Then it was placed in a 45°C high temperature box and vacuum-sealed after the electrolyte was fully infiltrated to obtain the battery of Example 2.
[0041] Comparative Example 1:
[0042] A soft-packaged square lithium carbon fluoride primary battery with a tab at the same end of the battery, which is composed of two wound square pole groups with dimensions of 3mm thick * 80mm wide * 100mm long connected in parallel internally, with a designed capacity of 7.8Ah. The schematic diagram of its internal structure is shown in Figure 5shown.
[0043] The wound square electrode group consists of a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet consists of a current collector and positive electrode powder, with a coating size of 107μm thick × 86mm wide * 588mm total length. A 15mm current collector empty foil is reserved at the winding insertion end and an aluminum pole ear is set. The pole ear size is 0.1mm thick × 12mm wide; the current collector is a 15μm thick carbon-coated aluminum foil; the positive electrode powder is composed of carbon fluoride, conductive agent and binder (the weight ratio of the three is 92:3:5), and the total double-sided positive electrode powder loading is 12mg / cm 2 The carbon fluoride therein is the same as the carbon fluoride in Example 1, and the gram capacity is 700 mAh / g.
[0044] The negative electrode sheet is continuous metallic lithium with dimensions of 0.05mm thick × 84mm wide * 610mm long. A nickel pole ear is set at the insertion end of the winding. The ear size is 0.07mm thick × 12mm wide. The nickel pole ear is bonded to the negative lithium sheet by a pressing process.
[0045] The diaphragm is made of polyethylene (PE) and has dimensions of 16 μm thick × 89 mm wide × 1300 mm long.
[0046] The positive electrode sheet, separator and negative electrode sheet are wound around a square winding needle with a thickness of 1.0 mm and a width of 74 mm, with the positive electrode ear and the negative electrode ear located at the same end of the electrode group and ended with a separator.
[0047] The two square electrode groups are stacked in the thickness direction, and the pole ears of the same polarity are stacked together. The 0.2mm thick * 20mm wide aluminum pole ear containing glue is connected to the positive pole ear of the electrode group, and the 0.2mm thick * 20mm wide nickel pole ear containing glue is connected to the negative pole ear of the electrode group by ultrasonic welding. Finally, the connected battery is placed in the pit of the stamped aluminum-plastic film shell, and a heat sealer is used to perform double-sided heat sealing, and the end reserved for injection is not sealed. The subsequent manufacturing process is the same as that of Example 1.
[0048] Comparative Example 2:
[0049] A soft-packaged square lithium carbon fluoride primary battery with a tab at the same end of the battery, which is composed of three cylindrical electrode groups with a diameter of 17.6 mm connected in parallel internally, with a designed capacity of 7.8 Ah. Except for the total double-sided loading of carbon fluoride and positive electrode powder of the electrode, the other manufacturing methods are basically the same as those in Example 1.
[0050] The fluorinated carbon used in this comparative example is conventional commercial fluorinated graphite, with an F / C ratio of 1.0, an average particle size of about 12 μm, and a total specific surface area of about 280 m 2 / g, gram capacity is 780mAh / g (10 hour rate discharge), the material has a large expansion rate after discharge, and F / C is uniform in the particles. The total double-sided loading of the positive electrode powder in the prepared positive electrode sheet is 10.8mg / cm 2 The thickness of the positive electrode sheet after rolling is 98μm.
[0051] Test example:
[0052] The batteries prepared in the above-mentioned Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to constant current discharge at room temperature at 0.1C (0.78A) and 0.5C (3.9A) respectively without external clamping, and the cut-off discharge voltage was 2.0V; and the thickness of the batteries before and after discharge was measured respectively; the batteries after discharge were disassembled in a dry environment, and the thickness of the positive and negative electrodes of the batteries after discharge was measured respectively. The above-mentioned test data are shown in Table 1, and the 0.5C discharge comparison curve is shown in Table 1. Figure 6 shown.
[0053] Table 1 is a comparison of the battery discharge data obtained in Examples 1 and 2 and Comparative Examples 1 and 2
[0054]
[0055] From the above comparative test results, it can be seen that the actual 0.1C discharge capacity of the batteries prepared by Example 1 and Example 2 at room temperature is basically the same as the designed capacity. The thickness expansion rate of the positive electrode sheet after full discharge is about 30%. Since the thickness of the negative electrode sheet is consumed during discharge, the diameter of the cylindrical electrode group hardly changes after discharge, or even slightly decreases, so the thickness of the battery does not change substantially. During 0.5C high-rate discharge, good electrode interface contact is maintained, and the multi-electrode ears achieve good electrical and thermal conductivity. The battery 0.5C discharge capacity retention rate is as high as more than 98%, and the battery surface temperature is lower than 70°C during discharge.
[0056] The battery prepared in Comparative Example 1 uses the same carbon fluoride, but is prepared using a conventional square structure and winding process. During the 0.1C discharge process without external clamping conditions, as the thickness of the positive electrode sheet increases, the distance between the electrode sheet and the diaphragm in the battery gradually increases, the reaction is uneven, and the thickness of the electrode sheet surface varies. There are gullies and reaction dead zones, resulting in the actual capacity of 0.1C being lower than the design value (the utilization rate is only 91%). During the 0.5C high-rate discharge, the increase in the distance between the positive and negative electrodes gradually increases the reaction polarization, and the internal temperature of the battery increases, resulting in battery swelling and a sharp decrease in the voltage platform, with a capacity utilization rate of only 70.8% (compared to the 0.1C capacity). In Comparative Example 2, although a cylindrical electrode group with multiple internal lugs is used, the carbon fluoride itself expands greatly during discharge. After 0.1C discharge, the positive electrode sheet expands by 90%. After full discharge, the diameter of the cylindrical electrode group expands significantly, the battery thickness increases significantly (22.4%), and the actual capacity is slightly lower than the designed capacity. Moreover, during 0.5C discharge, the conventional carbon fluoride material used in the battery has poor conductivity and large reaction polarization. The voltage drops rapidly during discharge, and the capacity utilization rate is only 83.4%.
[0057] The above comparative tests show that the soft-packaged lithium carbon fluoride primary battery provided by the present invention obtains a conventional square external size by connecting the internal cylindrical pole groups in parallel, adopts a lightweight and safe aluminum-plastic film shell, takes advantage of the close contact of the pole pieces in the cylindrical pole group, and achieves the good effect of close contact between the positive and negative pole pieces and the diaphragm during the discharge process by wrapping multiple turns of termination tape around the outer ring, thereby ensuring that the battery capacity is fully utilized. At the same time, the drainage structure design of multiple pole ears and foil pole ears not only achieves the effect of uniform distribution of current density and reduced polarization inside the battery, but also can quickly and effectively guide the heat inside the battery, thus overcoming the problem that lithium carbon fluoride batteries cannot discharge at high power. The present invention provides a high-power lithium carbon fluoride primary battery with high specific energy, safety and reliability, controllable appearance, and no need for clamping discharge. Its preparation process is simple and has very high industrial and commercial value.
[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A soft-packaged lithium carbon fluoride primary battery, characterized in that: It is composed of multiple cylindrical electrode groups, non-aqueous electrolyte, glue-containing pole ears and shells, wherein the multiple cylindrical electrode groups are in parallel relationship with each other; the cylindrical electrode group is composed of a positive electrode sheet, a negative electrode sheet and a separator; the outer ring of the cylindrical electrode group is wrapped with 2-5 turns of termination tape; the current collecting method of the positive electrode sheet and the negative electrode sheet is to set multiple pole ears for current collection or reserve continuous foil as pole ears for current collection; the current collecting pole ears of the positive electrode sheet and the negative electrode sheet are respectively located on both sides of the cylindrical electrode group along the axial direction; The active material of the positive electrode sheet is a mixture of carbon fluoride and an oxide with electrochemical activity, wherein the mass ratio of carbon fluoride in the mixture is 20%; the F / C atomic ratio in the carbon fluoride is 0.4-1.0, and the F / C atomic ratio is distributed in a gradient in the material particles, and the outermost layer of the material particles is carbon with good conductivity, and the thickness of the carbon layer is 1-20nm; the active material of the negative electrode sheet is a lithium alloy and pure metallic lithium, and the alloying elements of the lithium alloy include one or more of nickel Ni, cobalt Co, manganese Mn, aluminum Al, magnesium Mg, and zirconium Zr; The shell is a soft shell of aluminum-plastic film or steel-plastic film.
2. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The connection between the multiple tabs of the positive electrode sheet is carried out by busing with an aluminum strip, and the connection method between the tab or busing aluminum strip and the glue-containing tab is ultrasonic welding or laser welding.
3. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The multiple tabs of the positive electrode sheet are evenly arranged in the positive electrode sheet, and the tabs are connected to the positive electrode sheet current collector by ultrasonic welding process. The material of the tabs is aluminum; the positive electrode sheet current collector is aluminum foil or carbon-coated aluminum foil.
4. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The connection between the multiple tabs of the negative electrode sheet is carried out by busing with a nickel strip, a copper strip or a copper-nickel-plated strip, and the connection between the tab or busing strip and the glue-containing tab is ultrasonic welding or laser welding.
5. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The multiple tabs of the negative electrode sheet are evenly arranged in the negative electrode sheet, and are bonded to the negative electrode metal lithium by a pressing process, or connected to the negative electrode current collector by an ultrasonic welding process; the negative electrode current collector is copper foil; the material of the tabs is nickel, copper or copper plated with nickel.
6. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The reserved continuous foil is used as a current collector for the electrode tab, and the connection method between the reserved continuous foil electrode tab and the adhesive-containing electrode tab is ultrasonic welding or laser welding.
7. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The fluorinated carbon includes fluorinated hard carbon, fluorinated soft carbon, fluorinated amorphous carbon, fluorinated artificial graphite, fluorinated natural graphite, fluorinated graphene, fluorinated carbon fiber, fluorinated carbon nanotube, fluorinated carbon microsphere, fluorinated activated carbon or fluorinated carbon black.
8. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The carbon fluoride has been subjected to surface modification treatment, and the surface modification treatment method is a hydrothermal method or a plasma method.
9. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The electrochemically active oxides include manganese dioxide MnO2, nickel oxide NiO, copper oxide CuO, vanadium pentoxide V2O5, silicon oxide SiO2, Ag2V4O 11 One or more of .
10. The soft-packaged lithium carbon fluoride primary battery according to claim 1, characterized in that: The F / C atomic ratio in the fluorinated carbon is 0.75-0.95.
